Interactions among HIV gp120, CD4, and CXCR4: dependence on CD4 expression level, gp120 viral origin, conservation of the gp120 COOH- and NH2-termini and V1/V2 and V3 loops, and sensitivity to neutralizing antibodies. - Mondor, I; Moulard, M; Ugolini, S; Klasse, P; Hoxie, J; Amara, A; Delaunay, T; Wyatt, R; Sodroski, J; Sattentau, Q (1998)
The binding of HIV-derived recombinant soluble (s)gp120 to the CD4(+)/CXCR4(+) A3.01 T cell line inhibits the binding of the CXCR4-specific monoclonal antibodies 12G5, which interacts with the second extracellular loop, and 6H8, which binds the NH2 terminus. We have used this as an assay to analyse the interaction of recombinant sgp120 from diverse viral origins with CXCR4. The strength of the interaction between sgp120 and CXCR4 correlated with sgp120 affinity for the CD4-CXCR4 complex, and the interaction of sgp120MN and sgp120IIIB with CXCR4 was highly dependent on the level of CD4 expressed on a variety of different T cell lines. sgp120 from X4, R5X4, and R5 viruses interacted with CXCR4, although the R5 sgp120-CXCR4 interactions were weaker than those of the other gp120s. The interaction of sgp120IIIB or sgp120MN with CXCR4 was inhibited by neutralizing monoclonal antibodies that prevent the sgp120-CD4 interaction but also by antibodies specific for the gp120 V2 and V3 loops, the CD4-induced epitope and the 2G12 epitope, which interfere weakly or not at all with CD4-sgp120 binding. The binding to A3.01 cells of wild-type sgp120HxB2, but not of sgp120 deleted in the COOH and NH2 termini, interfered with 12G5 binding in a dose-dependent manner. Further deletion of the V1 and V2 loops restored CXCR4 binding activity, but additional removal of the V3 loop eliminated the gp120-CXCR4 interaction, without decreasing the affinity between mutated sgp120 and CD4. Taken together, these results demonstrate that the interactions between sgp120 and CXCR4 are globally similar to those previously observed between sgp120 and CCR5, with some apparent differences in the strength of the sgp120-CXCR4 interactions and their dependence on CD4.